Epithelial Cells Expressing EhADH, An Entamoeba histolytica Adhesin, Exhibit Increased Tight Junction Proteins - Betanzos, Abigail; Zanatta, Dxinegueela; Bañuelos, Cecilia; Hernández-Nava, Elizabeth; Cuellar, Patricia; Orozco, Esther (Frontiers in Cellular and Infection Microbiology, 2018)
In Entamoeba histolytica, the EhADH adhesin together with the EhCP112 cysteine protease, form a 124 kDa complex named EhCPADH. This complex participates in trophozoite adherence, phagocytosis and cytolysis of target cells. EhCPADH and EhCP112 are both involved on epithelium damage, by opening tight junctions (TJ) and reaching other intercellular junctions. EhADH is a scaffold protein belonging to the ALIX family that contains a Bro1 domain, expresses at plasma membrane, endosomes and cytoplasm of trophozoites, and is also secreted to the medium. Contribution of EhADH to TJ opening still remains unknown. In this paper, to elucidate the role of EhADH on epithelium injury, we followed two strategies: producing a recombinant protein (rEhADH) and transfecting the ehadh gene in MDCK cells. Results from the first strategy revealed that rEhADH reached the intercellular space of epithelial cells and co-localized with claudin-1 and occludin at TJ region; later, rEhADH was mainly internalized by clathrin-coated vesicles. In the second strategy, MDCK cells expressing EhADH (MDCK-EhADH) showed the adhesin at plasma membrane. In addition, MDCK-EHADH cells exhibited adhesive features, producing epithelial aggregation and adherence to erythrocytes, as described in trophozoites. Surprisingly, the adhesin expression produced an increase of claudin-1, occludin, ZO-1 and ZO-2 at TJ, and also the transepithelial electric resistance (TEER), which is a measure of TJ gate function. Moreover, MDCK-EhADH cells resulted more susceptible to trophozoites attack, as showed by TEER and cytopathic experiments. Overall, our results indicated that EhADH disturbed TJ from the extracellular space and also intracellularly, suggesting that EhADH affects by itself TJ proteins, and possibly synergizes the action of other parasite molecules during epithelial invasion.